Multifaceted promotion of apoptosis by acetylcholinesterase - Knorr, Debbra Y.; Demirbas, Defne; Heinrich, Ralf (Frontiers in Cell Death, 2023)
Elevated expression of acetylcholinesterase (AChE) is a common characteristic of apoptotic cells in both invertebrate and vertebrate species. While increased levels of AChE sensitize cells to apoptogenic stimuli, its absence or pharmacological inactivation interferes with apoptotic cell death. AChE may exert its pro-apoptotic function directly as an integral component of the apoptotic molecular machinery or indirectly by limiting the availability of receptor ligands and structural binding partners that promote cell survival under non-apoptogenic conditions. AChE promotes formation of the apoptosome and degrades DNA after nuclear accumulation. Its esterase activity limits the availability of acetylcholine as ligand for cell membrane-located nicotinic and muscarinic ACh-receptors and mitochondrial nicotinic ACh-receptors that normally support vital physiological states. Studies on insects suggest, that cytokine-activated cell-protective pathways may suppress AChE overexpression under apoptogenic conditions to prevent apoptotic cell death. We provide an overview of studies on various organisms and cell types that summarizes the contribution of AChE to the progress of apoptosis via multiple mechanisms.